Adult Narratives of the Psychosocial Impact of Cleft in a Western Australian Cohort. (March 2019) - Nicholls, Wendy; Persson, Martin; Robinson, Suzanne; Selvey, Linda
Background: Living with a cleft condition involves many years of multidisciplinary therapy, treatment, and surgical intervention. This complex process may have both physical and psychosocial long-term impacts. There is limited evidence of the psychosocial impact of cleft on individuals in Australia. Aim: To obtain an understanding of the adult patient perception of having a cleft and explore the impact of the condition on their lives. Design: Qualitative methodologies at one case study site in Western Australia. Population of Interest: Adults with a cleft lip and/or palate (CL/P) who had received treatment at Princess Margaret Hospital, the only treatment center for cleft in Western Australia. Methodology: Individual in-depth semi-structured qualitative interviews were conducted and recorded and transcribed for analysis. Results: Fifteen adults with a CL/P. Two main themes were identified: lived experience (with 3 subthemes: normality, support networks, and impacts in later life) and advice to others. The majority of participants reported social rejection and isolation, which occurred mostly at school and in some instances at home, but did not often last into adulthood. The greatest protective factor was the support of family and friends, which if missing during their childhood, was desired and appreciated in adulthood. Conclusion: Adults with CL/P may require psychosocial support from their cleft team including referral to clinicians in adult services. There is also the need for earlier psychological interventions and social programs to support those with appearance-related social difficulties.